Exploring the Relationship Between Lateral Thinking and Creativity - Crismono, Prima Cristi; Pambudi, Didik Sugeng; Lestari, Nurcholif Diah Sri; Suwito, Abi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study aims to analyze the relationship between lateral thinking ability and creativity among high school students. A total of 158 students were assessed using lateral thinking and creative thinking tests to evaluate their skills. The results revealed a significant positive correlation between these two abilities, indicating that students with higher lateral thinking scores tend to have better creative thinking scores. Linear regression analysis showed that lateral thinking skills could be a significant predictor of student creativity. However, despite the regression model indicating a strong relationship, some data variation suggests that other factors, such as motivation or learning environment, may also influence creativity. This study highlights the importance of lateral thinking skills in fostering creativity and provides recommendations for further research to consider additional variables and employ more complex modeling approaches